Pengukuran Usability pada Website SMK Ma'arif 3 Somalangu Kebumen Menggunakan System Usability Scale (SUS) - Khasan, Fahmi; Muflih, Ghufron Zaida (Jurnal Ilmiah Binary STMIK Bina Nusantara Jaya Lubuklinggau, 2022)
In the world of education, websites have a very important role in providing information related to the website owner's institution and can also be a medium for promotion. One of the websites we researched was the website of SMK Ma'arif 3 Somalangu. We consider that visitors or users also have a big influence on the website. Some of these reviews encourage us to choose the SUS (System Us-ability Scale) method in analyzing the use of the SMK Ma'arif 3 Somalangu website. From the results of measurements and analysis that have been carried out using SUS, the validity test states that it is valid with the results of Rhitung> Rtabel on the questionnaire items and in the Reliability test with the results of 0.637 which states the results are re-liable. The results showed that the score on the website of SMK Ma'arif 3 Somalangu is 97.43, which gets the predicate A, the Best Imaginable category, while the level of acceptance (feel) of visitors is margin high. The results describe that it is considered that the website of SMK Maarif 3 Somalangu is considered effective, efficient and satisfying for users/visitors and easy to use.